DESENVOLVIMENTO E CARACTERIZAÇÃO DE NANOCÁPSULAS CONTENDO ÓLEO DE CHIA - Martis, Elenice Spagnolo Rodrigues (2017)
Health care with skin and/or damage following trauma are considered specialized practices and recommended to the patient in all the world. In this context, topically application of the natural products as chia (Salvia hispânica L.) oil has shown promising alternative to treat wound, because the oil from its seed is rich in linolenic acid (omega 6 or n-6) linolenic acid (omega 3 or n-3). These essential fatty acids contribute to the skin healing, but they are instable in presence of light and oxygen. Because this, in the present study the promise is nanoencapsulate chia oil due its relevant characteristics for skin health and the potential benefit of the nanotechnology, with highlight to prevention the degradation of active compounds and potential increasing topic permeation. The aim is developing and characterize nanocapsules within chia oil and hydrophilic gel containing this nanocapsules. Previous study was performed to evaluate skin tolerance and product acceptability assessed using biometric measurements after topic application of the chia oil in natura. The nanocapsules production was performed according technique preformed polymer to the following procedure: one organic and another aqueous phase were prepared; organic solution was poured in aqueous that immediately results in the formation of nanoparticles. The physicochemical and structural characterizations were performed in the suspensions. The chia oil-nanocapsules within hydrogel formulation was produced and characterized. Chia oil in natura improved hydration and erythema of the skin evaluated by biometric. Chia oil-nanocapsules showed particle diameter of 246.23 ± 1.53 nm, polydispersity index of 0.148 ± 0.08, zeta-potential values were -3.84 ± 0.05 and pH 6.51 ± 0.12. The stability studies indicated that particle diameter of nanocapsules maintained almost unaltered following exposition during 120 days at different temperatures. Drug free nanocapsules showed similar results. Gas chromatography, 1H13C-NMR analyses confirmed the chemical identity of the majority components linolenic acid and linolenic acid in the products chia oil in natura and nanoencapsulated; these results proved the presence of chia oil into the nanoparticles. The viability assay was evaluated at VERO and melanoma cells after incubation with chia oil-free and nanocapsules formulations, and both linage cells did not show outcome effect of toxicity. The nanocapsules within hydrogel formulation displayed pleasant odor, white color (due presence of nanocapsules) and characteristic visual aspect of the gel (separation, creaming, and cracking). Physical stability of the chia oil-nanocapsules within hydrogel formulation was unaltered after exposition to lower temperature (± 4 ºC) during 120 days, 11 without change in odor, color and visual aspect. However, after exposure at higher temperature (± 25 ºC and ± 40 ºC) hydrogel formulation showed reduction on viscosity and pH following 15 and 30 days, respectively. Thus, the conclusion of present study is that the nanocapsules within chia oil is viable and stable. The study proved the potentiality and suitability of this novel system, but future investigations should be performed to determine therapeutic effect of the chia oil-nanocapsules incorporated into hydrogel for topically therapeutic purposes.